Promoting the Emotional and Behavioral Success of Youths A Practical Guide for Clinicians - Delgado, Sergio V.; Pedapati, Ernest V.; Strawn, Jeffrey R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Clinicians often have difficulty helping the parents of youth with emotional and behavioral difficulties and fail to recognize that often it is the youth s cognitive and learning weaknesses that drive their maladaptive behaviors. This book aims to help clinicians further understand the roots of youth s maladaptive behaviors. It also addresses the impact of youth s varied cognitive abilities on their behaviors and problems with self-esteem, particularly in youth that do not meet the diagnostic criteria for a formal learning disability. While many clinicians view learning deficits as impairments in specific academic skills, these deficits go beyond varied learning abilities and often experience difficulties in emotional, social, and behavioral functioning. These impairments vary from child to child and it is crucial to develop practical interventions for improved self-esteem and emotional success. Varied learning abilities reflect a neurodevelopmental problem in youth that can lead to difficulties with their emotional, social, and academic functioning and limit their intellectual potential. There are often treatment impasses when a youth s behavioral problems do not improve with traditional forms of psychotherapy and medication. The practical individualized interventions recommended in this book will: 1) decrease conflict in day-to-day interactions between youth and parents, 2) improve self-esteem and 3) help to achieve realistic social, emotional and academic goals. The text will help clinicians determine which maladaptive behaviors are a result of cognitive deficits and not symptoms of a disease-based mental disorder. Written by experts in the field, Promoting the Emotional and Behavioral Success of Youths reviews appropriate interventions in the context of the public health strategies that address the prevention of secondary socio-economic aspects as a result of cognitive weaknesses, such as realistic educational needs, career and employment choices. Clinicians will be able to use this book to develop best fit multimodal interventions to help parents of youth develop adaptive behaviors.
Introduction: Biological, Emotional and Social Development -- The Four Pillars of a Contemporary Diagnostic Interview -- Temperament: The Building Block of Personality -- Intelligence: Why don t you behave? -- Cognitive Flexibility (Theory of Mind): Being in your shoes -- Personality: My Friends Are Just Like Me -- Putting It All Together: Adapting to Youths Strengths and Weaknesses -- Parenting principles to help youths: Debunking common parenting myths.
Keywords: Psychiatry; Medicine and psychology; Mental health; Public health; Psychiatry; Behavioral Medicine; Mental Health; Public Health; Problem Behavior; Social Support; Adaptation, Psychological; Child; Adolescent